Silicotuberculosis: a critical narrative review - Rodney Ehrlich; Jill Murray; Qonita Said-Hartley; David Rees (European Respiratory Review)
Silicotuberculosis, the combination of silicosis and pulmonary tuberculosis (TB), remains a substantial clinical and public health problem in high TB burden countries with silica-exposed workforces. The objectives of this narrative review are to propose a definition of silicotuberculosis which includes post-tuberculous lung disease, to emphasise the importance of understanding how the two diseases modify each other, and to identify as yet unanswered questions relevant to clinical practice and disease control and mitigation. The unique aetiological relationship between silica exposure and TB is now firmly established, as is the accelerated impairment and mortality imposed by TB on individuals with silicosis. However, the rich clinical, pathology and laboratory literature on combined disease from the pre-TB treatment era appears to have been largely forgotten. The close clinical and pathological appearance of the two diseases continues to pose a challenge to imaging, diagnosis and pathological description, while inconsistent evidence regarding TB treatment and TB preventive treatment prevails. Many other topics raise questions to be answered, inter alia: the range of phenotypes of combined disease; the rates and determinants of disease progression; the role of computed tomography in identifying and characterising combined disease; appropriate screening practice; acceptable policies of management of workers that combine risk reduction with social security; and the workplace respirable silica concentration that protects against the excess TB attributable to inhaled silica.